Removing and reimplanting deep brain stimulation therapy devices in resistant OCD (when the patient does not respond): case report. Issue 1 (December 2016) - Real, Eva; Plans, Gerard; Alonso, Pino; Aparicio, Marco; Segalàs, Cinto; Cardoner, Narcís; Soriano-Mas, Carles; López-Solà, Clara; Menchón, José
Abstract Background Deep brain stimulation (DBS) is emerging as a promising tool in the treatment of refractory obsessive-compulsive disorder (OCD) but the search for the best target still continues. This issue is especially relevant when particularly resistant profiles are observed in some patients, which have been ascribed to individual responses to DBS according to differential patterns of connectivity. As patients have been implanted, new dilemmas have emerged, such as what to do when the patient does not respond to surgery. Case presentation Here we describe a 22-year-old male with extremely severe OCD who did not respond to treatment with DBS in the nucleus accumbens, but who did respond after explanting and reimplanting leads targeting the ventral capsule-ventral striatum region. Information regarding the position of the electrodes for both surgeries is provided and possible brain structures affected during stimulation are reviewed. To our knowledge this case is the first in the literature reporting the removal and reimplantation of DBS leads for therapeutical benefits in a patient affected by a mental disorder. Conclusion The capability for explantation and reimplantation of leads should be considered as part of the DBS therapy reversibility profile in resistant mental disorders, as it allows application in cases of non-response to the first surgery.